2021
DOI: 10.3389/fsurg.2021.745875
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Levels of Keratinocyte Growth Factor Are Significantly Elevated for 5 Weeks After Minimally Invasive Colorectal Resection Which May Promote Cancer Recurrence and Metastasis

Abstract: Background: Human Keratinocyte Growth Factor (KGF) is an FGF family protein produced by mesenchymal cells. KGF promotes epithelial cell proliferation, plays a role in wound healing and may also support tumor growth. It is expressed by some colorectal cancers (CRC). Surgery's impact on KGF levels is unknown. This study's purpose was to assess plasma KGF levels before and after minimally invasive colorectal resection (MICR) for CRC.Aim: To determine plasma KGF levels before and after minimally invasive colorecta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 71 publications
(128 reference statements)
0
1
0
Order By: Relevance
“…FGF7 is also called keratinocyte growth factor (KGF); Visco et al (2009) confirmed that KGF and its receptors directly influence intestinal epithelial growth and differentiation regulation ( Visco et al, 2009 ). It prevents intestinal mucosal barrier disruption; however, KGF overexpression can cause abnormal intestinal epithelial cell proliferation and may lead to colorectal cancer ( Finch and Rubin, 2004 ; Shantha Kumara et al, 2021 ). Therefore, intestinal epithelial cell hyperproliferation may explain the association between FGF7 and constipation.…”
Section: Discussionmentioning
confidence: 99%
“…FGF7 is also called keratinocyte growth factor (KGF); Visco et al (2009) confirmed that KGF and its receptors directly influence intestinal epithelial growth and differentiation regulation ( Visco et al, 2009 ). It prevents intestinal mucosal barrier disruption; however, KGF overexpression can cause abnormal intestinal epithelial cell proliferation and may lead to colorectal cancer ( Finch and Rubin, 2004 ; Shantha Kumara et al, 2021 ). Therefore, intestinal epithelial cell hyperproliferation may explain the association between FGF7 and constipation.…”
Section: Discussionmentioning
confidence: 99%